2002
DOI: 10.1038/sj.bjc.6600484
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring communication in consultations with women from high risk breast cancer families

Abstract: This multicentre study examined the influence of patient demographic, disease status and psychological variables on clinical geneticists/genetic counsellors (consultants) behaviours in initial consultations with women from high-risk breast cancer families. One hundred and fifty-eight women completed a pre-clinic self-report questionnaire. The consultations were audiotaped, transcribed verbatim and coded. Consultants did not vary their behaviour according to women's expectations. However, significantly more asp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
66
2

Year Published

2003
2003
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(73 citation statements)
references
References 39 publications
5
66
2
Order By: Relevance
“…Perhaps, consultants are not exploring women's agendas in sufficient detail, nor following through on information at this point. In another analysis of these data reported elsewhere, we found that consultants were not responsive to women's expectations or their level of psychological distress prior to the consultation (Lobb et al, 2002b).…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…Perhaps, consultants are not exploring women's agendas in sufficient detail, nor following through on information at this point. In another analysis of these data reported elsewhere, we found that consultants were not responsive to women's expectations or their level of psychological distress prior to the consultation (Lobb et al, 2002b).…”
Section: Discussionmentioning
confidence: 52%
“…This study is one component of a larger randomised controlled trial of providing women with an audiotape of their genetic counselling consultation (Lobb et al, 2002a), and the influence of patient characteristics on consultants' communication (Lobb et al, 2002b). Staff at each of the participating clinics invited women to participate in the study (between November 1998 andMay 2000) when they telephoned to make their appointment.…”
Section: Methodsmentioning
confidence: 99%
“…This does not acknowledge the interactive features and the many other topics and goals that characterise the counselling process, which may also affect subsequent perceptions and behaviours (see Lobb et al, 2002). The effect of breast cancer history on worry after counselling illustrates this point: apparently, an element other than the objective risk information provided in the counselling increased the worry in affected women relative to unaffected women.…”
Section: Discussionmentioning
confidence: 99%
“…13 Moreover, counselors direct the communication, initiate the discussion of most topics, 14 and seldom build on the counselee's perspective, i.e., her needs, knowledge, and risk perception. 15,16 By providing pre-visit education, more consultation time might be left to discuss the counselee's decision and counselees can be helped to request information. 14 Studies of computer-based pre-visit information for breast cancer genetic counselees indeed indicate that the focus within the consultation shifted away from basic education toward more counselee-specific information about risk, decision making, and preventive options.…”
Section: Introductionmentioning
confidence: 99%